Hello,
Answer A
s(x)=3x-7
s(2t-4)=3*(2t-4)-7=6t-12-7=6t-19
<em>Look</em><em> </em><em>at</em><em> </em><em>the</em><em> </em><em>attached</em><em> </em><em>picture</em><em> </em><em>⤴</em>
<em>Hope</em><em> </em><em>it</em><em> </em><em>will</em><em> </em><em>help</em><em> </em><em>u</em><em>.</em><em>.</em><em>.</em>
Answer:14
Step-by-step explanation: minus *minus = + so its +27
and then you just do the maths 27-13=14
Answer: For y it's y=4x−12 and for x it's x=12+y/4
Step-by-step explanation:
SOLVING FOR X
8x-2y=24
2(4x−y)=24
4x−y=24/2
4x−y=12
4x=12+y
x=12+y/4
SOLVING FOR Y
8x-2y=24
2(4x−y)=24
4x−y=24/2
4x−y=12
−y=12−4x
y=−12+4x
y=4x−12
Hope this helps, have a BLESSED AND WONDERFUL DAY! As well as a great Black History Month and Valentine's day! :-)
- Cutiepatutie ☺❀❤
Answer:
Step-by-step explanation:
8 I think